Gambaran pengetahuan dokter gigi di rsgm ladokgi Tni al r.e martadinata dalam ketepatan penulisan odontogram - Fathiah Devi Syaharani; Rizki Tanjung; Vanessa Utama (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: All medical practitioners and dentists are required to create medical records. Medical record writing must be in accordance with established regulations, because it has a very important role as written evidence in court. Odontogram is a part of the dental medical record which contains information about a person's teeth and is a reliable means of identifying teeth. At present not all dentists and dental nurses in Indonesia have properly recorded odontogram medical records, there is still no uniformity in writing or terminology used in odontograms. Purpose: This study aims to obtain an overview of the level of knowledge of dentists at RSGM LADOKGI TNI AL R.E MARTADINATA in odontograms writing accuracy. Method: Descriptive observational study with cross sectional design conducted through online. The data collected from 47 respondents, all are dentists who working in RSGM LADOKGI TNI AL R.E MARTADINATA. A questionnaire used to measure the dentists’ knowledge, it consists of 15 closed-ended questions. Result: Based on the result of research data calculation, 30 respondents (63,8%) have good knowledge (76%-100%), 12 respondents (25,5%) have sufficient knowledge (56%-75%), and 5 respondents (10,7%) have deficient knowledge (less than 55%). Conclusion: Most of the dentists at RSGM LADOKGI TNI AL R.E MARTADINATA have a good knowledge in odontograms writing accuracy.